Analisis Tujuh Tokoh Hierarki Bertingkat Dalam Novel 7 Sayap Pendosa Karya Jienara (Kajian Teori Kepribadian Humanistik Abraham Maslow) - Irchamna, Achmad Maulana (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Humanistic Psychology is a scientific approach theory that focuses on problems of individual human behavior. Based on this, this research focuses on the study of humanistic psychology in the novel 7 Wings of Pendosa by Jienara. This research focuses on several needs found according to Abraham Maslow's humanistic psychology studies. The aim of this research is to determine the personality of each character in the novel 7 Wings of Pendosa by Jienara based on the humanistic psychology study of Abraham Maslow. The research method used in this research is a qualitative descriptive method. The results of the analysis are based on Abraham Maslow's humanistic psychological theory which includes five aspects of character needs, namely: (1) Physiological needs, (2) Safety needs, (3) Love and belonging needs, (4) Self-esteem needs, and (5) The need for self-actualization is fulfilled in the character's personality.